2016
DOI: 10.1177/1932296816642577
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing for Teens With Diabetes

Abstract: Background: Adolescence is a developmental period associated with increased difficulty managing diabetes. During adolescence family functioning, including miscarried helping, family conflict, and acceptance of illness, is an important predictor of adherence to treatment recommendations. Multiple barriers exist to receiving behavioral health interventions to address suboptimal adherence. We hypothesized that behavioral family systems therapy–diabetes (BFST-D) delivered via telehealth would yield changes in fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In total, the literature search resulted in the selection of 29 studies that met the inclusion criteria. [1][2][3][4]7,9,11,12,[14][15][16][17]20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The search and screening process is shown in the PRISMA flow diagram ( Supplementary Fig. S1).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, the literature search resulted in the selection of 29 studies that met the inclusion criteria. [1][2][3][4]7,9,11,12,[14][15][16][17]20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The search and screening process is shown in the PRISMA flow diagram ( Supplementary Fig. S1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies were conducted in 13 different countries, with the majority of services from the United States (n = 15, 52%). 1,4,7,17,[26][27][28][29][30][33][34][35][36]39,40 The most common study type was a randomized controlled trial (RCT) (n = 11, 38%). 3,7,11,16,17,20,25,28,30,31,37 Most studies were conducted over 24 weeks (n = 9, 31%), 1,4,[15][16][17]20,26,27,31 with the minimum study length at 12 weeks, 3,12,26 and the maximum study length at 240 weeks.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that glycemic and psychologic outcomes from telemedicine visits were equivalent to or better than in-person visits for both children and adults with type 1 diabetes (T1D). [11][12][13][14][15] When behavioral family systems therapy for teenagers with diabetes was delivered using a videoconferencing service, overall family conflict was reduced and parents reported improved acceptance of illness. 12 In another study on 18-55-year-old patients with T1D, there was a tendency toward less impact of diabetes on quality of life in the group receiving telemedicine visits (P = 0.061).…”
Section: Virtual Education and Medical Visitsmentioning
confidence: 99%
“…[11][12][13][14][15] When behavioral family systems therapy for teenagers with diabetes was delivered using a videoconferencing service, overall family conflict was reduced and parents reported improved acceptance of illness. 12 In another study on 18-55-year-old patients with T1D, there was a tendency toward less impact of diabetes on quality of life in the group receiving telemedicine visits (P = 0.061). 13 Additional benefits of telemedicine were increased attendance at visits, 15,16 less time spent traveling to and attending visits, 11,13,17,18 and lower cost.…”
Section: Virtual Education and Medical Visitsmentioning
confidence: 99%